Aesthetics of immediacy: reflections on an ethical-philosophical foundation of the work of Gaston Bachelard - Martínez, Arturo (2022)
Although Bachelard’s entire philosophy of imagination is affected by a symbolic materialism which can play a mediating role in reverie’s path, it is also true that the purpose of art, especially in poetry, is the search for truth, the lightning flash of insight, the deep apprehension of being itself, an experience that can hardly be given if we interpose, between the being of the thing/object and human subject, concepts or categories that seek a higher comprehension of the operational phenomena at stake, but which ultimately drown the saying of what is being shown to us. The poetic image must be a vehicle capable of symbolizing reality by connecting it with the imaginary, while being at the same time that uncaused force which brings about the ontological novelty capable of building a new anthropocosmos.